The Role of Biodegradable Magnesium and Its Alloys in Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis Based on Animal Studies - Shang, Zhizhong; Li, Dongliang; Chen, Jinlei; Wang, Mingchuan; Zhang, Baolin; Wang, Xin; Ma, Bin (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: The actual efficacy of magnesium and its alloy in anterior cruciate ligament reconstruction (ACLR) was systematically evaluated to reduce the risk of translation from animal experiments to the clinic. Methods: Databases of PubMed, Ovid-Embase, Web of Science, CNKI, Wanfang, VIP, and CBM were searched for literature in July 2021. Screening of search results, data extraction, and literature quality evaluation were undertaken independently by two reviewers. Results and discussion: Seven articles were selected for the meta-analysis. The results showed that the mechanical properties of the femoral-tendon graft–tibia complex fixed with magnesium and its alloys were comparable to those fixed with titanium and its alloys, and magnesium and its alloys were superior to titanium and its alloys in promoting new bone formation. In addition, the unique biodegradability made magnesium and its alloys an orthopedic implant with significant therapeutic potential. However, whether the degradation rate of magnesium and its alloy can match the rate of bone-tendon integration, and whether the bioconjugation of bone-tendon after degradation can meet the exercise load still needs to be explored in further detail. Simultaneously, it is necessary for future research to improve and standardize experimental design, result measurement, etc., so as to minimize the risk of transforming animal experimental results into clinical practice.